New records of the primarily Sri Lankan Pseudophilautus regius (Manamendra-Arachchi & Pethiyagoda, 2005) (Amphibia; Rhacophoridae) from the Eastern Ghats of India, crossing the Palk Strait saltwater barrier in the Indian Ocean - B, Bharath.; Dinesh, K. P.; M, Karuthapandi.; Kunte, Kalyani Bai; Shabnam, A.; Jaiswal, Deepa; Jadhav, S.s. (Zootaxa, 2024)
Pseudophilautus regius is a bush frog originally described from the dry zones of Sri Lanka. In the present study, P. regius is being reported from the Eastern Ghats of Andhra Pradesh, India as a new record for the country. The Indian population of P. regius being polytypic, identity confirmation was aided by genetic data. Earlier data for the genus Pseudophilautus indicated that three endemic species were known from the Western Ghats, India and 75 endemic species occurred in Sri Lanka. This report forms the first report of a bush frog exhibiting distribution in both India and Sri Lanka across the saltwater barrier of the Palk Strait in the Indian ocean. Discussions are made regarding other lineages which have distributions across both India and Sri Lanka.